Molecular dynamics simulation of thermal welding process of Ag nanoparticles. (17th August 2020) - Ren, Xiaoying; Li, Xiao; Huang, Chenchen; Yin, Hailong; Wei, Fengqi
Abstract: The thermal welding process of Ag nanoparticles was studied by molecular dynamics using embedded atoms method (EAM), and the melting point of Ag nanoparticles was analyzed by radial distribution function (RDF) and root mean square displacement (RMSD). The results show that for Ag nanoparticles with diameter less than 10 nm, driven by surface energy, the welding temperature will be much lower than the melting point when the spacing between nanoparticles is smaller than the radius of particle, the mechanism at low temperature is different from that at high temperature. The spontaneous rotation of nanoparticles during welding at suitable temperature makes the lattice orientation parallel to each other in three-dimensional space, which may be caused by collision of nanoparticles or short-range interaction near the surface. From the thermodynamic point of view, this behavior is driven by the reduction of surface energy, with the increase of temperature, the interface between particles will become chaotic gradually.